Feeding Anglo-Saxon England (FeedSax): Digital Data Archive - McKerracher, M; Hamerow, H; Bogaard, A; Hodgson, J; Charles, M; Ramsey, C; Thomas, R; Forster, E; Stroud, E; Neil, S; Holmes, M; Roushannafas, T (University of Oxford, 2022)
The Feeding Anglo-Saxon England project (FeedSax: 2017-2022) used bioarchaeological methods to address longstanding questions about the development of medieval field systems. To this end, FeedSax created a large collection of archaeological data - both compiled from existing sources, and newly created through primary analyses - pertaining to charred plant remains, animal bones, stable isotopes, radiocarbon dates, and pollen records. The FeedSax digital archives includes the resultant datasets in CSV and Excel formats as well as a SQL database ('Haystack'), along with accompanying SQL queries and documentation in MS Word format. The archive is deposited with the Archaeology Data Service (https://doi.org/10.5284/1057492).